Promising Neutrophil-Associated Biomarkers in Lung Diseases of Patients with Antisynthetase Syndrome and Dermatomyositis - Lei Liu; Jundi Wang; Peiyu Zhang; Wenjia Sun; Xiuliang Zhu; Xiujuan Sun; Jing Xue; Huaxiang Wu (Journal of Immunology Research)
Objectives. Antisynthetase syndrome (ASS) and dermatomyositis (DM) are serious autoimmune diseases, with lungs being the most frequently involved organ and sometimes fatal. This study is aimed at clarifying the role of neutrophil-associated biological markers in suggesting ASS and DM-associated respiratory infections and interstitial lung diseases. Methods. We carried out a retrospective review of the medical records of 46 cases of ASS and DM diagnosed at the Second Hospital of Zhejiang University College of Medicine, between January 2017 and December 2020. Serum myeloperoxidase (MPO), neutrophil elastase (NE), α1 anti-trypsin (AAT), and interleukin-6 (IL-6) were also detected. Results. Gottron’s sign is characteristic of dermatomyositis, while polyarthritis is more characteristic of ASS. Pulmonary function is worse in ASS than in DM patients. Patients with ASS and DM had abnormal lymphocyte and neutrophil counts compared to healthy subjects, but not in relation to lung function and rapid progression of interstitial lung disease (RP-ILD). Elevated serum NE, MPO, and IL-6 levels are suggestive of respiratory infections, whereas decreased circulating IL-6 is predictive of RP-ILD. Conclusion. Our study identified the neutrophil-associated biomarkers MPO, NE, and IL-6 as promising indicators with different suggestive roles in respiratory infections and interstitial lung diseases in patients with ASS and DM.